2001
DOI: 10.1007/s11746-001-0266-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and γ‐linolenic acid accumulation in strains of zygomycetes growing on glucose

Abstract: Strains of Zygomycetes, belonging to the genera Zygorhynchus, Mortierella, Rhizopus, Mucor, and Cunninghamella, when cultivated on glucose produced significant quantities of γ‐linolenic acid (GLA). After exhaustion of the nitrogen source from the culture medium, all strains accumulated cellular lipids in concentrations ranging from 10 to 28% (oil/dry mycelium). However, in some strains after the depletion of the carbon source (glucose) from the culture medium, a reconsumption of the accumulated oil and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 17 publications
8
88
0
5
Order By: Relevance
“…In a similar manner, when Mucor circinelloides CBS 172-27 was cultured on sunflower oil, during storage lipid breakdown unsaturated fatty acids were preferentially oxidized [6]. In contrast, other Zygomycetes (genera Rhizopus, Cunninghamella and Zygorhynchus) preferentially oxidized C18:0, while γ-linolenic acid ( ∆6,9,12 C18:3) content increased during storage lipid breakdown [20,21]. Likewise, oleaginous bacteria of the genus Rhodococcus, which had accumulated both TAGs and polyhydroxyalkanoates (PHAs), preferentially mobilized TAGs whereas PHAs breakdown was delayed [22].…”
Section: Discussionmentioning
confidence: 88%
“…In a similar manner, when Mucor circinelloides CBS 172-27 was cultured on sunflower oil, during storage lipid breakdown unsaturated fatty acids were preferentially oxidized [6]. In contrast, other Zygomycetes (genera Rhizopus, Cunninghamella and Zygorhynchus) preferentially oxidized C18:0, while γ-linolenic acid ( ∆6,9,12 C18:3) content increased during storage lipid breakdown [20,21]. Likewise, oleaginous bacteria of the genus Rhodococcus, which had accumulated both TAGs and polyhydroxyalkanoates (PHAs), preferentially mobilized TAGs whereas PHAs breakdown was delayed [22].…”
Section: Discussionmentioning
confidence: 88%
“…As for GLA, it was found in remarkable quantities in all lipid fractions, especially in P fraction, reaching up to 21.4%, 19.9%, and 19.8% in Z. moelleri, C. echinulata, and Mucor sp., respectively. These fungi are known as GLA producers [3,6,7,17,47]. P is the site of PUFA production [16] and therefore its fatty acid composition provides a description concerning desaturase activity in the mycelium.…”
Section: Fatty Acid Composition Of Lipid Fractionsmentioning
confidence: 99%
“…Oleaginous Zygomycetes have the ability to accumulate large amounts of lipids (namely single cell oils-SCO) rich in polyunsaturated fatty acids (PUFA) [1][2][3][4][5][6][7][8][9][10], which are of significant pharmaceutical and nutritional value. Among PUFA, γ-linolenic acid (GLA) is of particular interest as it is known for its selective killing of tumor cells without harming normal cells [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on Mortierella and other fungi have shown that media variables such as different carbon and nitrogen sources, pH of the growth medium and the composition of trace elements affect the growth and lipid accumulation that occur within various species [3,4,5,6] . Of particular importance is the effect of metal ions on lipid and GLA production.…”
Section: Introductionmentioning
confidence: 99%